STUDI LITERATUR: HUBUNGAN POLA KONSUMSI MAKANAN GORENGAN DENGAN PENYAKIT KARDIOVASKULAR - Izdihar Hanifa; Ibnu Zaki; Farida Farida (JURNAL RISET GIZI, 2020)
Background: Cardiovascular disease occurred by many factors, one of them is because of consuming high saturated fat intake from fried food. Previous studies have shown that there are inconsistent results from the research related to the correlation between fried food intake and cardiovascular disease. This literature study is important to be done to explain the problem of different results for each previous study.Objective: To examine the correlation between fried food intake and cardiovascular disease from various previous studies also to analyze the correlation between fried food intake people with polymorphisms of ALDH2 and ABCA1 genes and cardiovascular disease occurrence.Methods: Exploring literature material was done by Pubmed and Science Direct databases. Article research methods were sought by observational studies (cross-sectional, case-control, and cohort). Eight articles were selected based on the inclusion criteria that have been determined.Results: Fried food intake is associated with cardiovascular diseases such as coronary heart disease, ischemic heart disease, and heart failure. However, the EPIC-Spanish cohort study shows that fried food intake is not associated with cardiovascular disease. People with polymorphisms carrier in the ALDH2 gene rs671 genotypes A/A and A/G has a higher risk of increase CHD compared to a person who is a GG genotype carrier. People with polymorphism carrier in the ABCA1 gene rs4149339 genotype CC also has a higher risk of developing CHD compared with people who carry a TT genotype.Conclusion: Fried food intake has a positive correlation with the risk of cardiovascular disease in adulthood and the elderly. Fried food intake with people who have a certain gene variations is associated with cardiovascular disease occurrence.